INDUSTRIAL METHODS OF CULTIVATION OF STERLET (ACIPENSER RUTHENUS) IN THE CONDITIONS OF DAGESTAN - Magomed A. Mammayev; Magomed M. Shikhshabekov; Nukhkadi I. Rabazanov; Magomed S. Kurbanov; Magomed K. Mirzakhanov; Ruslan M. Mammayev; Shakhrudin A. Gunashev (Юг России: экология, развитие, 2017)
Aim. The aim of the research is to study the influence of various environmental factors (abiotic and biotic) on some fish-biological indicators in the cultivation of sturgeons with the use of a recirculating aquaculture system (RAS). Methods. A complete biological analysis was carried out according to the generally accepted ichthyological methods. Monitoring of the hydrochemical regime in the RAS was carried out throughout the study period. The temperature and pH of water were measured daily and the concentration of oxygen in the basins was measured three times a day. Results. Taking into account that the fish specimens studied did not show any pathology and also taking into consideration their genetic homogeneity and absolutely identical conditions in the RAS, the findings obtained can be explained by the different degree of oxygen supply under artificial growth conditions. The results of the biochemical analysis show that the blood of fish grown in the RAS with an elevated oxygen content (experimental group) by the end of the experiment (4 weeks) contains an increased amount of malondialdehyde (MDA) which could lead to the observed difference in the dynamics of growth parameters of the young of the year. Conclusions. When the oxygen content of the water is below 70% the growth rate slows down, as food consumption is almost halved, while the saturation of O2 by 40% is considered critical. When sterlet is grown to produce a high mass, it is necessary to set the temperature of the water in the pools in the interval of 21-220°C in the ultrasonic complexes. For industrial cultivation of sterlet, we recommend using a planting density of 60 kg/m3.